2018
DOI: 10.1002/pam.22071
|View full text |Cite
|
Sign up to set email alerts
|

What Interventions Work Best for Families Who Experience Homelessness? Impact Estimates from the Family Options Study

Abstract: What housing and service interventions work best to reduce homelessness for families in the United States? The FamilyOptions Study randomly assigned 2,282 families recruited in homeless shelters across 12 sites to priority access to one of three active interventions or to usual care in their communities. The interventions were long-term rent subsidies, short-term rent subsidies, and transitional housing in supervised programs with intensive psychosocial services. In two waves of follow-up data collected 20 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(112 citation statements)
references
References 41 publications
3
103
0
1
Order By: Relevance
“…We argue that student homelessness is similarly a consequence of conscious policy choices. The negative relationship we found between housing vouchers and literal homelessness contributes to a growing body of research finding that housing and cash assistance programs are indeed an effective means for combating homelessness (Gubits et al 2018;Shaefer et al 2019). Moreover, we found that an increase in rental costs was associated with an increase in doubling up.…”
Section: Sensitivity Analysismentioning
confidence: 53%
See 2 more Smart Citations
“…We argue that student homelessness is similarly a consequence of conscious policy choices. The negative relationship we found between housing vouchers and literal homelessness contributes to a growing body of research finding that housing and cash assistance programs are indeed an effective means for combating homelessness (Gubits et al 2018;Shaefer et al 2019). Moreover, we found that an increase in rental costs was associated with an increase in doubling up.…”
Section: Sensitivity Analysismentioning
confidence: 53%
“…Indeed, homeless mothers appear to be no more likely than housed poor mothers to have mental health or substance use problems, and the two groups have similar levels of educational attainment, work experience, and criminal histories (Culhane et al 2007). On the other hand, sources of instability related to domestic violence (Bassuk, Perloff, and Dawson 2001;Fertig and Reingold 2008), the birth of a severely ill child (Curtis et al 2010(Curtis et al , 2013, unstable employment (Edin and Shaefer 2015;Gubits et al 2018), and paternal incarceration (Wildeman 2014) may explain why some poor families become homeless, whereas others do not.…”
Section: Explanations For Child and Family Homelessnessmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 10 trials on income-assistance interventions, including rental assistance, [47][48][49][50][51][52][53][54][55][56] financial empowerment, 47 social enterprise interventions, 48 individual placement and support, 48,54 and compensated work therapy. 52 Our systematic review showed the benefit that income-assistance interventions have on housing stability (Gary Bloch, University of Toronto, Toronto, Ont., and Vanessa Brcic, University of British Columbia, Vancouver, BC: unpublished data, 2020).…”
Section: Evidence Summarymentioning
confidence: 99%
“…The success of behavioral interventions ranges from increasing college enrollment among graduating seniors (Oreopoulos & Ford, 2019) and reducing homelessness via short‐term rent subsidies (Gubits et al., 2018) to reducing the risk of lead paint exposure among children (Bae, 2012) and the promotion of energy savings through implementation of “smart” thermostat technologies (Harding & Lamarche, 2016). Reviews of hundreds of interventions in the health (Byerly et al., 2018) and pro‐environmental behavior domains (Vlaev et al., 2016) point to the importance of such interventions in changing behavior.…”
Section: Theorymentioning
confidence: 99%